A Lively Afterlife and Beyond : The Soul in Plato, Homer, and the Orphica - Radcliffe G. Edmonds III (Études Platoniciennes)
The NeoPlatonist Olympiodorus claims that “Plato borrows everywhere from Orpheus”, but many of the afterlife ideas which Plato is supposed to have drawn from “Orphism” come not from the Orphica, but from the broader mythological tradition. Even those elements which Plato did draw from the Orphica or similar sources, however, he transformed in significant ways to suit his philosophical purposes in the particular dialogue. I first examine the idea, which appears in many different sources from the earliest evidence, of a lively afterlife, an idea that differs from the epic vision of Homer where poetic glory provides the only meaningful form of life after death. Nevertheless, a differentiated afterlife with judgement, complex geography, and rewards and punishments was a widespread and generally accepted idea, which Plato manipulates in various ways in different dialogues. By contrast, other ideas of the relation of the soul to the body, such as the soul entombed in the body or the process of reincarnation, appear marked, in the evidence of Plato and others, as extra-ordinary and unfamiliar ideas, which Plato again transposes to fit his arguments in the dialogue.